The Concept of Grammatical Organon in the Star of Redemption by Rosenzweig - Ilya Dvorkin (MDPI AG, 2021)
In his book The Star of Redemption, F. Rosenzweig formulated a new philosophical system, which is based not on thinking, or being, but on language. At the same time, Rosenzweig not only postulates language but deduces it as a procedural reality that is currently unfolding in relation to perfect and closed elements—the world, God and man. Language fundamentally changes our attitude not only toward the world, God and man but in general toward all objects of knowledge and action. The world ceases to be perceived as an equal given, a person ceases to be a generic definition for subjectivity and acquires singularity and uniqueness. God is not defined as the Absolute Reality but becomes a live interlocutor. One of the central points of Rosenzweig’s system is its grammatical organon—a method that allows one to consider linguistic processes. Rosenzweig unfolds his organon in three books of the second part of The Star of Redemption. This article discusses the philosophical foundations of Rosenzweig’s grammatical organon and the features of its application to various linguistic and speech phenomena.